Internet-based cognitive behavioral therapy for psychological symptoms during the final phase of the COVID-19 pandemic: a feasibility study - Aminoff, Victoria; Björklund, My; Ekström, Elina; Stenback, Andrea; Yousafzai, Uzma; Berg, Matilda; Ludvigsson, Mikael; Andersson, Gerhard (Frontiers in Digital Health, 2025)
IntroductionSARS-CoV-2 and the accompanying COVID-19 pandemic had a great impact on people's well-being, both physically and mentally. The pandemic continued to affect people even after its end was declared. Internet-based cognitive behavioral therapy (ICBT) is a psychological treatment alternative that is effective for several types of psychological symptoms and conditions. This study aimed to investigate the feasibility of ICBT for psychological symptoms related to the COVID-19 pandemic in adults aged 18 years and older during the final phase of the pandemic. Since the psychological impact of the pandemic varies among individuals, individually tailored ICBT was examined, in which participants receive different treatment content based on their needs.MethodsA within-group study was conducted with 24 participants, receiving individually tailored ICBT during eight weeks with weekly support from a therapist. Participants received one module per week, which was selected based on the participant's specific symptoms and needs. Of the 24 participants, 16 (66.7%) were assessed as probably meeting the diagnostic criteria for post-COVID syndrome. Pre- and post-treatment measurements using self-report questionnaires for several psychological symptoms were administered online.ResultsStatistically significant improvements were observed in symptoms of depression, anxiety, post-traumatic stress, loneliness, and exhaustion. Small increases were observed in a measure of CBT knowledge, whereas no significant changes were found in stress, quality of life, experience of cognitive failures, and economic stress. Participants completed on average 3.96 out of 8 modules, with five (20.8%) completing all modules. Fifteen (62.5%) of the 24 participants completed the post-treatment measurement. Three participants (12.5%) withdrew from the study.ConclusionOverall, the results indicate that individually tailored ICBT with weekly support from a therapist is a feasible treatment for psychological symptoms related to the COVID-19 pandemic in its final phase. However, larger studies with more participants are needed to draw further conclusions regarding the effects of ICBT during the final phase of a pandemic. The treatment could be further developed to benefit a broader range of participants.